1999
DOI: 10.1021/es990279n
|View full text |Cite
|
Sign up to set email alerts
|

The Medieval Metal Industry Was the Cradle of Modern Large-Scale Atmospheric Lead Pollution in Northern Europe

Abstract: There is great concern for contamination of sensitive ecosystems in high latitudes by long-range transport of heavy metals and other pollutants derived from industrial areas in lower latitudes. Atmospheric pollution of heavy metals has a very long history, and since metals accumulate in the environment, understanding of present-day pollution conditions requires knowledge of past atmospheric deposition. We use analyses of lead concentrations and stable lead isotopes ( 206 Pb/ 207 Pb ratios) of annually laminate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
133
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 221 publications
(143 citation statements)
references
References 33 publications
9
133
0
1
Order By: Relevance
“…We found a remarkable consistency between our Pb record and the pollution Pb profiles of varved lakes in eastern Sweden, where the pre-industrial Pb fallout was mainly sourced from mainland Europe and from the British Isles (Brännvall et al, 1999; Fig. 2).…”
supporting
confidence: 76%
See 2 more Smart Citations
“…We found a remarkable consistency between our Pb record and the pollution Pb profiles of varved lakes in eastern Sweden, where the pre-industrial Pb fallout was mainly sourced from mainland Europe and from the British Isles (Brännvall et al, 1999; Fig. 2).…”
supporting
confidence: 76%
“…The NaOH-extraction and AMS-14 C measurements for nine selected core 25 depths were conducted at the Poznań Radiocarbon Laboratory, Poland (Goslar et al, 2004). In addition, we compared our bulk sediment Pb profiles with the Pb fallout records from varved lakes in Sweden (Brännvall et al, 1999) to constrain the chronology.…”
Section: Geochronological Methods 15mentioning
confidence: 99%
See 1 more Smart Citation
“…However significant increase of heavy metals in sediments, especially Pb and Cd is caused by long distance atmospheric transportation (Pacyna 1987;Braennvall et al 1999). This study has shown that sediments of the studied lakes are polluted with heavy metals.…”
Section: Figmentioning
confidence: 70%
“…Serving as evidence of the biogeochemical significance of dust additions, these anthropogenic constituents are now found accumulating in environments where dust is a major sedimentary input (e.g. Brännvall et al, 1999;Le Roux et al, 2004;.…”
Section: Introductionmentioning
confidence: 99%